"Progressive Kofinanzierung" und GAP-Reform 2013 - Markus F. Hofreither (Universität für Bodenkultur Wien, Department für Wirtschafts- und Sozialwissenschaften, Institut für nachhaltige Wirtschaftsentwicklung, 2010)
– Considerations regarding the structure of the CAP after 2013 are well underway. A key issue in this respect is the future of decoupled direct payments (DDP) in the first pillar, which represent the bulk of support for EU agriculture. The 'Options Paper' of the EU Commission indicates that first pillar payments in diversified form will remain part of the CAP after 2013. The size of the future budget is still uncertain, yet the level of the decoupled base premium is expected to be significantly lower. In this case the "progressive" co-financing mechanism being developed in this paper, which builds on the economic performance of member states, could provide an option for first pillar payments.
Keywords: H23; Q18; 330; CAP Reform; fist pillar; base payment; co-financing